The Application of Cultural Ecology Principles to the Conservation Strategy for the Jakarta Cathedral Church Area as a Cultural Heritage Site - Dominikus Demon Tereng; Prisca Bicawasti Budi Sutanty (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
This study aimed to identify and analyze the preservation strategies of the Jakarta Cathedral Church area as a cultural heritage site in adapting to a tropical climate, using a cultural ecology approach. a neo-Gothic architectural landmark that is over a century old and faces preservation challenges due to tropical climatic conditions as well as increasing urban pressures. This research employed a descriptive qualitative method, utilizing field observations, semi-structured interviews with site managers and restoration practitioners, documentation, and literature review. The findings indicate that the applied preservation strategies have integrated the principles of cultural ecology with the regulatory framework of Law No. 11 of 2010 through spatial organization, material selection, construction techniques, and zoning systems. However, implementation is still limited, especially in addressing tropical climate conditions, as reflected in the imbalance between material authenticity, construction methods, and environmental performance. The findings demonstrate that cultural heritage preservation should be understood as an adaptive and integrated system encompassing physical, cultural, and environmental dimensions, rather than just technical interventions. The study strengthens the role of the cultural ecology as an analytical framework in architectural conservation studies, particularly within the context of historical sites in tropical regions facing simultaneous environmental pressures and urban development.